INCREASE OF OPERATION EFFICIENCY OF THERMAL FURNACES OF RESISTANCE IN CONDITIONS OF OAO «MAZ» - I. A. Trusova; A. I. Mihluk; D. V. Mendelev; P. E. Ratnikov (Литьë и металлургия, 2011)
The estimation of economic efficiency of lining replace in hardening-tempering aggregate StZa-5.40.5,715L-B1 of OAO «Minsk automobile plant» is carried out in the present article.